A revision of the Old World species of Leptopsilopa Cresson (Insecta: Diptera: Ephydridae) - Zatwarnicki, Tadeusz; Cielniak, Magdalena; Pochrząst, Katarzyna (Zootaxa, 2016)
Diagnoses and illustrations of three Leptopsilopa species known in the Old World: L. africana Cresson, L. mutabilis Cresson and L. pollinosa (Kertesz) are provided. Three new synonyms are proposed: L. aurata (Canzoneri and Meneghini) and L. tibialis (Canzoneri and Meneghini) = L. africana; Psilopa confeteae Canzoneri and Munari = L. pollinosa. Three other species are removed from Leptopsilopa and combined with Athyroglossa, as A. leonensis (Canzoneri and Rampini), new combination, A. mianii (Canzoneri) new combination and A. rossii (Canzoneri and Raffone), new combination.